(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
This study presents the role of the geothermal waters mainly for the municipal heating, greenhouses, swimming pools, etc. Presently, two types of geothermal waters are used in the world. Waters of the temperatures higher than 130oC (steam) used mostly to drive turbines in geothermal power plants. Waters of low temperatures (20oC to 100oC) are used as a direct energy carrier for the municipal heating systems. The geothermal waters in Poland are presented in this paper.